Effectiveness of Bedside Leucodepletion Filter in Multi-Transfuse Thalassemia Patients (Mugda Medical College Journal, 2026)
Multi-transfused thalassemia patients are prone to transfusion-related complications. Febrile nonhemolytic transfusion reactions (FNHTR) are a relatively common complication associated with allogenic transfusions. As leucocytes have been implicated in the mechanism of FNHTR, it has been proposed that the transfusion of leucodepleted RBCs should be associated with a decreased incidence of FNHTR. Currently, the best leucodepletion can be achieved using leucodepletion filter. A quasi-experimental study was carried out between March 2019 and August 2021 in the Department of Transfusion Medicine of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, to evaluate the effectiveness of bedside leucodepletion filter in decreasing febrile nonhemolytic transfusion reactions (FNHTR) in multi-transfused thalassemia patients. We adopted a purposive sampling method. A total of 84 transfusion dependent thalassemia patients were included in this study according to inclusion and exclusion criteria and divided equally into two groups – intervention group and comparison group. Allocation of intervention was performed by non-randomized alternate assignment. The intervention group received packed red blood cells using leucodepletion filters, while the comparison group received packed red blood cells with conventional blood transfusion filters. The incidence of FNHTR was evaluated between these two groups. The mean age was 19.11±16.54 years in the intervention group and 15.79±10.83 years in the comparison group. Females were predominant in both groups, i.e., 59.5% and 54.8% in intervention group and comparison group respectively. Among adverse reactions, 21(25%) of the patients experienced chills and rigors – 2(4.8%) in the intervention group and 19(45.2%) in the comparison group. Other symptoms were only observed in the comparison group such as fever (38.1%), vomiting (4.8%), myalgia (7.1%), hypotension (2.4%) and skin rash (2.4%). Only 2(4.8%) patients had FNHTR in intervention group, while 25(59.5%) in comparison group experienced FNHTR. FNHTR was observed significantly lower (OR=29.4; CI=5.72–100) in the intervention group (p